Pengaruh Kualitas Audit Dan Manajemen Laba Terhadap Nilai Perusahaan - Anthony Holly; Robert Jao; Natalya Thody (STIE Jambatan Bulan, 2023)
The purpose of this study is to investigate the effect of audit quality and earnings management on firm value. The population used is all manufacturing companies in the consumer goods industry sector listed on the IDX with the 2018-2020 research period. The number of samples used is 103 companies selected using purposive sampling method and using secondary data. The analytical method used is the multiple regression analysis. The results of the analysis show that audit quality has a significant negative effect on earnings management. Earnings management has a significant positive effect on firm value. Audit quality has a significant positive effect on firm value.